Blurred: Selves Made and Selves Making - Oberg, Andrew, (Value Inquiry Book Series ;, 2021)
The question of the self, of what the self is (or even if there is a self), has been one that has grown alongside humanity - has haunted humanity - throughout our history. Blurred: Selves Made and Selves Making guides the reader down these dark corridors, shining light on the specters of theories past and unveiling a new self-view to hover afresh, beckoning to roadways beyond. In this remarkably interdisciplinary study, philosophy of mind joins with contemporary neuroscience and cutting-edge psychology to lay bare the how of identity formation, judgment, and behavior generation. Drawing on thinkers from both the Continental and Analytic traditions, consciousness is explored and a uniquely realist self-concept presented that, if adopted, offers a life lived otherwise.